Once Lured (a Riley Paige Mystery--Book #4) - Blake, Pierce (Lukeman Literary, 2016)
"A masterpiece of thriller and mystery! The author did a magnificent job developing characters with a psychological side that is so well described that we feel inside their minds, follow their fears and cheer for their success. The plot is very intelligent and will keep you entertained throughout the book. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) ONCE LURED is book #4 in the bestselling Riley Paige mystery series, which begins with the #1 bestseller ONCE GONE (Book #1)-a free download, with over 500 five star reviews! Women are turning up dead on a lone stretch of highway in Delaware. Some go missing for an inexplicable length of time, while others are turning up dead, their bodies left out for display in bizarre and mysterious ways. When a pattern is discovered, it becomes clear to the FBI that a twisted serial killer is on the hunt-luring girls in devious schemes-and that he won't stop killing, ever. The FBI, desperate to crack the case, urges Special Agent Riley Paige to take it on. But the brilliant Riley, still reeling from past cases, has finally found peace in her home life, and is determined to help her daughter April get back on her feet. Yet when the murders become too disturbing, too urgent-and when her former partner Bill implores her-Riley finally realizes she can't say no. Riley's hunt leads her deep into the unsettling world of hitchhikers, of drifters, of women that no one else cares for. When she discovers that several women are being kept alive and that there is still time to save them, she realizes she will stop at nothing, obsessing over the case and driving herself to the brink. Yet Riley realizes her own life is falling apart, and her own fragile psyche can barely handle the strain. In a frantic race against time, she will have to plunge deep into the killer's mind to save these women-and to save herself-from collapse. A dark psychological thriller with heart-pounding suspense, ONCE LURED is book #4 in a riveting new series-with a beloved new character-that will leave you turning pages late into the night. Book #5 in the Riley Paige series will be available soon.
Keywords: Krimi, detektivky